2014
DOI: 10.1093/mnras/stu343
|View full text |Cite
|
Sign up to set email alerts
|

WTS-2 b: a hot Jupiter orbiting near its tidal destruction radius around a K dwarf

Abstract: We report the discovery of WTS-2 b, an unusually close-in 1.02-day hot Jupiter (M P = 1.12M J , R P = 1.363R J ) orbiting a K2V star, which has a possible gravitationally-bound M-dwarf companion at 0.6 arcsec separation contributing ∼ 20 percent of the total flux in the observed J-band light curve. The planet is only 1.5 times the separation from its host star at which it would be destroyed by Roche lobe overflow, and has a predicted remaining lifetime of just ∼ 40 Myr, assuming a tidal dissipation quality fac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 107 publications
(127 reference statements)
1
42
1
Order By: Relevance
“…Fig. 12 (left) shows the distribution of the orbital distance to the Roche limit ratio (a/a R ) as a function of the planetary mass for the known transiting planets with 0.2 M Jup < M p < 13 M Jup and P < 12 d. WASP-121 b is one of the closest systems to tidal disruption, its direct competitors being WASP-12 b (Hebb et al 2009), WASP-19 b (Hebb et al 2010), WASP-103 b (Gillon et al 2014), OGLE-TR-56 b (Konacki et al 2003;Adams et al 2011), and WTS-2 b (Birkby et al 2014). According to Matsumura et al (2010), these extreme planets are now expected to undergo tidal orbital decay through tidal dissipation inside the star only (we will elaborate on this in Section 5.2 in the case of WASP-121 b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fig. 12 (left) shows the distribution of the orbital distance to the Roche limit ratio (a/a R ) as a function of the planetary mass for the known transiting planets with 0.2 M Jup < M p < 13 M Jup and P < 12 d. WASP-121 b is one of the closest systems to tidal disruption, its direct competitors being WASP-12 b (Hebb et al 2009), WASP-19 b (Hebb et al 2010), WASP-103 b (Gillon et al 2014), OGLE-TR-56 b (Konacki et al 2003;Adams et al 2011), and WTS-2 b (Birkby et al 2014). According to Matsumura et al (2010), these extreme planets are now expected to undergo tidal orbital decay through tidal dissipation inside the star only (we will elaborate on this in Section 5.2 in the case of WASP-121 b).…”
Section: Discussionmentioning
confidence: 99%
“…Combining the Matsumura et al's expression for da/dt and the Kepler's third law, we can calculate the current rate of orbital period change: (dP/dt) 0 = −0.0035 (10 6 /Q ,0 ) s yr −1 for P , 0 = 0.89 d and (dP/dt) 0 = −0.0118 (10 6 /Q ,0 ) s yr −1 for P , 0 = 1.13 d. We can then estimate how long it would take to observe significant transit timing variations (TTVs) due to the orbital decay of the planet using, e.g. the equation 7 of Birkby et al (2014). We note that this estimation assumes a constant rate of orbital period change dP/dt = (dP/dt) 0 .…”
Section: Orbital Evolution Of Wasp-121 Bmentioning
confidence: 99%
See 1 more Smart Citation
“…The decaying orbital period is expected to be observed through transit timing. For some planets, the cumulative shift in transit times may be about 10 2 s after ten years (Birkby et al 2014). Tentative detections of the orbital decay were reported for the systems OGLE-TR-113 and WASP-43 (Adams et al 2010;Blecic et al 2014), but have not been confirmed by further observations (Hoyer et al 2016;Jiang et al 2016).…”
Section: Introductionmentioning
confidence: 91%
“…This object consists of a gas giant (mass 1.4 M Jup , radius 1.7 R Jup ) transiting an F-type star (mass 1.3 M , radius 1.7 R ) every 1.21 days (Southworth 2012). The comparatively large component radii and short orbital period make OGLE-TR-56 a good candidate for the detection of tidally-induced orbital decay (Birkby et al 2014). This is potentially detectable by measuring the progressively earlier occurrence of transits compared to a linear ephemeris, by an amount which is predicted to be roughly 30 s over a decade (Birkby et al 2014).…”
Section: Photometric Stabilitymentioning
confidence: 99%